Diet and lifestyle risk factors associated with incident hypertension in women - Forman, John P. (2009)
CONTEXT: Hypertension is an important preventable risk factor for death among women. While several modifiable risk factors have been identified, their combined risk and distribution in the population has not been assessed. OBJECTIVE: To estimate the hypothetical fraction of hypertension associated with dietary and lifestyle factors in women. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study of 83,882 adult women aged 27-44 years in the second Nurses’ Health Study who were free from hypertension, cardiovascular disease, diabetes, and cancer in 1991, and who had normal reported blood pressures (defined as 120/80 or less), with follow-up for incident hypertension for 14 years through 2005. We identified 6 modifiable lifestyle and dietary factors for hypertension and defined 6 low risk categories: body mass index (BMI) <25 kg/m(2), a daily mean of 30 minutes of vigorous exercise, a DASH style diet, modest alcohol intake up to 10 g/day, non-narcotic analgesic use less than once per week, and intake of 400 μg/day or more of supplemental folic acid. We analyzed the association between combinations of three (normal body mass index, daily vigorous exercise, and DASH style diet), four (three low risk factors plus modest alcohol intake), five (four low risk factors plus avoidance of analgesics), and six (addition of folic acid supplements) low risk factors and the risk of developing hypertension. MAIN OUTCOME MEASURES: Adjusted hazard ratios (HRs) for incident self-reported hypertension and population attributable risks. RESULTS: A total of 12,319 incident cases of hypertension were documented. All six modifiable factors were independently associated with the risk of developing hypertension during follow-up after also adjusting for age, race, family history of hypertension, smoking status, and use of oral contraceptives. For women who had all six low-risk factors (0.3% of the population), the hazard ratio for incident hypertension was 0.22 (95% CI, 0.10-0.51); the hypothetical population attributable risk (PAR) was 78% (95% CI, 49-90%) for women who lacked these low-risk factors. The corresponding hypothetical absolute incidence rate difference (ARD) was 8.37 cases per 1000 person-years. The PARs were 72% (95% CI, 57-82%; ARD=7.76) for 5 low risk factors (0.8% of the population), 58% (95% CI, 46-67%; ARD=6.28) for 4 low risk factors (1.6% of the population), and 53% (95% CI, 45-60%; ARD=6.02) for 3 low risk factors (3.1% of the population). BMI alone was the most powerful predictor, with BMI ≥25 kg/m(2) having an adjusted PAR of 40% (95%CI, 38%-41%) compared with BMI <25 kg/m(2). CONCLUSION: Adherence to low-risk dietary and lifestyle factors was associated with a significantly lower incidence of self-reported hypertension. Adopting low risk dietary and lifestyle factors has the potential to prevent a large proportion of new onset hypertension occurring among young women.